Copyright Protection On Trademarks In Digital Business - Icha Nurgamar (Penerbit Hellow Pustaka, 2025)
Advances in information and communication technology have succeeded in setting aside trade, the emergence of trade with new systems has created a view towards trade with the emergence of digital trade or e-commerce. Information and communication technology produces internet technology, this technology provides various conveniences which not only provide benefits to copyright but also cause losses which have an impact on increasing violations of copyright law in Indonesia, especially digital copies properly. Violations of copyright law give rise to various problems that require legal protection. Legal protection regarding copyright is based on digital technology, this gives rise to Law Number 19 of 2012 concerning Copyright.